Fake Drugs - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Faking and counterfeiting occurs throughout the world with claims that it is more common in some developing countries with weak regulatory programs. It is estimated that more than 10% of drugs worldwide are counterfeit, with up to 50% in some countries. Heightening vigilance and awareness of counterfeiting is one measure for combating faking.Rationale:The aim of this study was to document perceptions of various healthcare providers regarding the problem of drugs faking/counterfeiting including perceived levels, affected drugs, implications, and measures to control; thus, this study aims to provide empirical data on the perception of healthcare providers regarding counterfeit drugs and their effect on public health/safety.Materials and Methods:Ethical approval was obtained and pretested questionnaires were administered to consenting healthcare providers in six local government areas in Lagos. The collected data was sorted and entered into Microsoft Excel, following which analysis was carried out. Results are presented as tables and charts.Results:Respondents believed that the problem of fake/counterfeit drugs is common with a modal faking range of 41–50% of drugs in the country. Anti-infectives, anti-malarials, and analgesics were reported to be the most implicated drugs. Many believed that faking/counterfeiting of drugs can be surmounted by the promulgation and enforcement of appropriate legislation and closure of open drug markets.Conclusions:It can be concluded that respondents are aware of the challenges posed by counterfeit drugs and if empowered can serve as a tool in its eradication. It is recommended that appropriate modalities to review the existing laws and close open drug markets be put in place.